Dynamic enterprise architecture : how to make it work - Wagter, Roel (J. Wiley, 2005)
This book presents an approach to enterprise architecture, which enables corporations to achieve their business objectives faster. Focusing on the governance of IT in the organization, it provides tangible tools, advice and strategies for implementing and designing the architectural process within a corporation that will make a major contribution in driving the business forward and achieve its goals.